Design of Z-copy controlled-gain voltage differencing current conveyor based adjustable functional generator. Issue 2 (February 2015) - Sotner, Roman; Jerabek, Jan; Herencsar, Norbert; Dostal, Tomas; Vrba, Kamil
Abstract This paper introduces interesting active element and its application in the field of square and triangular wave generators. Active element, so-called Z-Copy Controlled Gain Voltage Differencing Current Conveyor (ZC-CG-VDCC), has availability of three mutually independently and electronically adjustable parameters (transconductance, intrinsic resistance of the current input terminal and current gain between two terminals) that are very popular for control of applications today. In addition, a proposed device utilizes very useful z-copy (additional auxiliary terminal) features and two terminals providing voltage difference. All mentioned features are beneficial in mixed-mode circuit synthesis and design of adjustable applications (active filters, oscillators, generators, modulators, etc.). Electronically adjustable properties of the device are involved in the design of an adjustable generator. The generator provides voltage- and current-mode square wave outputs that can be also used for differential square wave output when very simply modified. Application of the generator in simple pulse width modulator (PWM) is also introduced. A detailed analysis and Spice simulation results are given and main features of the circuits are compared to electronically controllable solutions of recent development in this field.